Analysis of badminton research trend in the last three decades: bibliographic analysis of Scopus journal database - Muchamad Arif Al Ardha; Nurhasan Nurhasan; Oce Wiriawan; Mochamad Purnomo; Andhega Wijaya; Nur Ahmad Arief; Sri Wicanhyani; Nur Salsabila Rhesa Pandhadha PUTRA; Sauqi Sawa Bikalawan; Chung Bing Yang; Kukuh Pambuka Putra (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Badminton has become a sport that has grown rapidly in the last few decades. The goal of the study is to examine how badminton research has evolved over the past 30 years. The Bibliometric Analysis and Systematic Review method was applied in this study. A thorough approach was used to scan SCOPUS research journal databases for articles. The term "Badminton" was utilized. Furthermore, journals published within the last 30 years starting in 2023 were excluded from consideration. On October 17th, 2023, 1,053 items from Scopus were extracted. As a result, 217 articles were chosen for additional examination using the VOS viewer computer program. The study's findings demonstrated that over the past 20 years, there has been a notable increase in interest in badminton research. China, Spain, England, and Japan have contributed the most to this research. English dominates in scientific publications about badminton, although several other languages ​​also contribute. Research subjects include athlete physiology, injuries, and health, as well as differences in playing styles and athlete rankings. Several studies have also highlighted the use of technology in-game analysis and athlete training. Research on badminton is an important part of the development of this sport and can support athletes' performance and health. In the next few decades, multidisciplinary research involving different languages ​​and countries may be the key to a more comprehensive understanding of the sport of badminton.